Talking politics in everyday family lives. Issue 1 (3rd April 2017) - Nolas, Sevasti-Melissa; Varvantakis, Christos; Aruldoss, Vinnarasan
ABSTRACT: How do children encounter and relate to public life? Drawing on evidence from ethnographic fieldwork conducted between 2014 and 2016 for the ERC-funded Connectors Study on the relationship between childhood and public life, this paper explores how children encounter public life in their everyday family environments. Using the instance of political talk as a practice through which public life is encountered in the home, the data presented fill important gaps in knowledge about the lived experience of political talk of younger children. Working with three family histories where political talk was reported by parents to be a practice encountered in their own childhoods and one which they continued in the present amongst themselves as a couple/parents, we make two arguments: that children's political talk, where it occurs, is idiomatic and performative; and that what is transmitted across generations is the practice of talking politics. Drawing on theories of everyday life developed by Michel de Certeau and others we explore the implications of these findings for the dominant social imaginaries of conversation, and for how political talk is researched.